Meningkatkan Pengalaman Museum melalui Realitas Tertambah: Studi Kasus Museum Pos Indonesia - Gozali, Alfian Akbar; Prawita, Fathah Noor; A, Subaveerapandiyan; Kusuma Handoyo, Amanda Putri; Assyifa, Cynthia (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2024)
This paper presents the development and implementation of Mussia AR, an interactive augmented reality (AR) application designed for the Indonesian Postal Museum. Aimed at enhancing the educational and engagement aspects of museum visits, this project addresses the need for innovative approaches in museum experiences. We followed an Extreme Programming methodology for the development, ensuring a user-centric and iterative approach. The application overlays digital information onto physical exhibits, providing visitors with an immersive and informative experience. Our development process included comprehensive user needs analysis, application design, implementation, and extensive testing for both functionality and user experience. The results from user testing indicate a significant improvement in visitor engagement and satisfaction. The application not only succeeded in providing an enhanced learning experience but also demonstrated the potential of AR technology in cultural and educational settings. Future recommendations include expanding the content, introducing multilingual support, and extending the application's compatibility to various platforms. Mussia AR stands as a testament to the effective use of AR in enriching educational experiences in museums.